Scaling Evidence-Based Interventions to Improve the Cardiovascular Health of People With Serious Mental Illness - Yuan, Christina T.; McGinty, Emma E.; Dalcin, Arlene; Goldsholl, Stacy; Dickerson, Faith; Gudzune, Kimberly A.; Jerome, Gerald J.; Thompson, David A.; Murphy, Karly A.; Minahan, Eva; Daumit, Gail L. (Frontiers in Psychiatry, 2022)
People with serious mental illnesses (SMIs) experience excess mortality, driven in large part by high rates of cardiovascular disease. Interventions designed to improve the cardiovascular health of people with SMI have been shown to lead to clinically significant improvements in clinical trials; however, the uptake of these interventions into real-life clinical settings remains limited. Implementation strategies, which constitute the “how to” component of changing healthcare practice, are critical to supporting the scale-up of evidence-based interventions. And yet, implementation strategies are often poorly described and rarely justified theoretically in the literature, limiting the ability to tease apart why, what, how, and when implementation strategies lead to improvement. We describe the implementation strategies that the Johns Hopkins ALACRITY Center for Health and Longevity in Mental Illness is using to scale-up three evidenced-based interventions related to: (1) weight loss; (2) tobacco smoking cessation treatment; and (3) hypertension, dyslipidemia, and diabetes care for people with SMI. Building on concepts from the literature on complex health interventions, we focus on considerations related to the core function of an intervention (i.e., or basic purposes of the change process that the health intervention seeks to facilitate) versus the form (i.e., implementation strategies to carry out core functions that are customized to local contexts). By clearly delineating how implementation strategies are operationalized to support the interventions’ core functions across these studies, we aim to build and improve the future evidence base of how to adapt, implement, and evaluate interventions to improve the cardiovascular health of people with SMI.